New bathymetry of the Linosa volcanic complex from multibeam systems (Sicily Channel, Mediterranean Sea). Issue 2 (3rd July 2019) - Tonielli, Renato; Innangi, Sara; Di Martino, Gabriella; Romagnoli, Claudia
ABSTRACT: This paper presents new bathymetric data acquired around Linosa Island, in the Pelagie Archipelago, revealing the submarine extension of the volcanic edifice, more wide and complex than previously known. The seafloor of Linosa, from the coastal area to about 1000 m depth, was mapped with multibeam systems during the 'Linosa 2016' and 'BioGeoLin 2017' surveys. A bathymetric map of the surveyed area (about 298 km 2 ) was drawn at the original 1:30, 000 scale. Overall, the submarine portions of Linosa extend on a total area of about 159 km 2 and are preferentially developed in a NW-SE direction, in agreement with the regional main tectonic trend in the area. The new bathymetric data allow to recognize different sectors in the submarine extension of the volcanic edifice where constructional (volcanic) activity alternates with erosive-depositional processes affecting the submarine flanks of the island.